2018
DOI: 10.1021/acs.jmedchem.8b00060
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Based Drug Discovery of Potent Protein Kinase C Iota Inhibitors

Abstract: Protein kinase C iota (PKC-ι) is an atypical kinase implicated in the promotion of different cancer types. A biochemical screen of a fragment library has identified several hits from which an azaindole-based scaffold was chosen for optimization. Driven by a structure-activity relationship and supported by molecular modeling, a weakly bound fragment was systematically grown into a potent and selective inhibitor against PKC-ι.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…An important study by Kwiatkowski et al identified an azaindole-based scaffold for the development of more potent and specific PKC-ι inhibitors. They described fragmented based approach an introduced a new class of potential aPKC inhibitors based on azaindole [90].…”
Section: Author Detailsmentioning
confidence: 99%
“…An important study by Kwiatkowski et al identified an azaindole-based scaffold for the development of more potent and specific PKC-ι inhibitors. They described fragmented based approach an introduced a new class of potential aPKC inhibitors based on azaindole [90].…”
Section: Author Detailsmentioning
confidence: 99%
“…Availability of biochemical or biophysical assays to understand SAR is critical in hit-to-lead step. This strategy has been proven to be successful in numerous targets such as developing bacterial Gyrase B inhibitors (Figure 2; Colony-stimulating factor 1 Computational approach Machiraju et al, 2019 Bruton's Tyrosine Kinase Mass spectrometry Hopkins et al, 2019 The atypical protein kinase C-iota Thermal shift assay Kwiatkowski et al, 2018Kwiatkowski et al, , 2019 Latency-associated nuclear antigen SPR, DSF Kirsch et al, 2019 Monoamine oxidase X-ray crystallography Cheng et al, 2019 Myeloid cell leukemia 1 NMR Murray J.B. et al, 2019;Szlávik et al, 2019 β-ketoacyl-ACP synthases X-ray crystallography Patterson et al, 2020 VEGFR-2 Computational design Zhang et al, 2019 West Nile viral protease STD-NMR Schöne et al, 2017 Transcriptional repressor EthR2…”
Section: Growing Of Fragment Hitsmentioning
confidence: 99%
“…Heterobiaryl compounds, especially those containing nitrogen, are very important structural units which are widely existed in many pharmaceuticals and biologically active moleculers . Transition‐metal‐catalyzed coupling reactions of aryl halides with heteroaryl organometallic reagents such as heteroaryl zinc reagents, heteroaryl magnesium reagents, heteroaryl aluminum reagents and heteroaryl boron reagents are important ways to construct these compounds.…”
Section: Introductionmentioning
confidence: 99%